Decrypting phytomicrobiome of the neurotoxic actinorhizal species, Coriaria myrtifolia, and dispersal boundary of Frankia cluster 2 in soil outward compatible host rhizosphere - Swanson, Erik; Sbissi, Imed; Ktari, Amir; Cherif-Silini, Hafsa; Ghodhbane-Gtari, Faten; Tisa, Louis S.; Gtari, Maher (Frontiers in Microbiology, 2022)
The actinorhizal plant, Coriaria myrtifolia is a neurotoxic plant species endemic to the western Mediterranean area, which forms a nitrogen-fixing symbiosis with members of Frankia cluster 2. Contrarily to other Frankia clusters, the occurrence and mode of dispersal for infective cluster 2 units outside of the host plant rhizosphere remains controversial. The present study was designed to investigate the structure of the microbiomes of C. myrtifolia phytosphere, rhizosphere and soil samples extending outward linearly up to 1km. Results showed that the epiphyte and endophyte communities were not significantly different for most of the plant tissues. C. myrtifolia phytomicrobiomes were dominated by Cyanobacteria for leaf, stem, and fruit while Actinobacteria and Proteobacteria were dominate in the root and nodule organelles. Nodule, as a special niche for nitrogen fixation, was mainly inhabited by Frankia but contains several non-Frankia bacteria. Beside Frankia cluster 2, the presence of clusters 1, 4 and large numbers of cluster 3 strains have been detected in nodules, roots, and rhizospheres of C. myrtifolia. Despite being found in all plots using plant trapping bioassays with C. myrtifolia seedlings, Frankia cluster 2 was not detected in soil metagenomes showing the limits of detection by this approach. This result also suggests that in the absence of appropriate host plant species Frankia cluster 2 has a reduction in the number of infective units present in the soil outward from the rhizosphere.